Transcriptomic analysis of primary nasal epithelial cells reveals altered interferon signalling in preterm birth survivors at one year of age - Evans, Denby J.; Hillas, Jessica K.; Iosifidis, Thomas; Simpson, Shannon J.; Kicic, Anthony; Agudelo-Romero, Patricia (Frontiers in Cell and Developmental Biology, 2024)
Introduction: Many survivors of preterm birth (<37 weeks gestation) have lifelong respiratory deficits, the drivers of which remain unknown. Influencers of pathophysiological outcomes are often detectable at the gene level and pinpointing these differences can help guide targeted research and interventions. This study provides the first transcriptomic analysis of primary nasal airway epithelial cells in survivors of preterm birth at approximately one year of age.Methods: Nasal airway epithelial brushings were collected, and primary cell cultures established from term (GA>37w) and very preterm participants (<32 weeks). Ex vivo RNA was collected from brushings with sufficient cell numbers and in vitro RNA was extracted from cultured cells, with bulk RNA sequencing performed on both the sample types. Differential gene expression was assessed using the limma-trend pipeline and pathway enrichment identified using Reactome and GO analysis. To corroborate gene expression data, cytokine concentrations were measured in cell culture supernatant.Results: Transcriptomic analysis to compare term and preterm cells revealed 2874 genes differentially expressed in ex vivo samples and 848 genes differentially expressed in cultured basal cell samples. Over one third of differentially expressed genes were related to host immunity, with interferon signalling pathways dominating the pathway enrichment analysis and IRF1 identified as a hub gene. Corroboration of disrupted interferon release showed that concentrations of IFN-α2 were below measurable limits in term samples but elevated in preterm samples (19.4 [76.7] pg/ml/µg protein, p=0.03). IFN-γ production was significantly higher in preterm samples (3.3 [1.5] vs 9.4 [17.7] pg/ml/µg protein; p=0.01) as was pg/ml/µg protein, p=0.01).Conclusions: Host immunity may be compromised in the preterm nasal airway epithelium in early life. Altered immune responses may lead to cycles of repeated infections, causing persistent inflammation and tissue damage which can have significant impacts on long-term respiratory function.